11, 11, 12, 12‐tetracyano‐9, 10‐anthraquinonedimethane as a sustainable cathode for room temperature all solid‐state lithium battery. (19th January 2022) - Shi, Weibo; Wang, Jiayao; Zhang, Xinyi; Wang, Qingli; Deng, Wenwen
Summary: Organic electrode materials have attracted extensive attention because of their high flexibility and sustainability, but their application was limited by the disadvantage of dissolution in conventional electrolyte. Here, we designed an all solid‐state lithium‐ion battery (ASSLIB) with 11, 11, 12, 12‐tetracyano‐9, 10‐anthraquinonedimethane (TCAQ) as the cathode and lithium metal as the anode. The solid electrolyte consisted of Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO)/polyoxyethylene(PEO) and lithium bis(trifluoromethanesulfonimide) (LiTFSI) salt. The Li||TCAQ ASSLIB delivered a discharge specific capacity of 83 mAh g −1 at a current density of 17 mA g −1 with a capacity retention of 72.2% after 100 cycles. Our research provided a new organic cathode material for high‐performance ASSLIBs. Abstract : We designed an all solid‐state lithium‐ion battery (ASSLIB) with 11, 11, 12, 12‐tetracyano‐9, 10‐anthraquinonedimethane (TCAQ) as the cathode and lithium metal as the anode. The ASSOLB can deliver a capacity of 84.4 mAh g −1 at 0.1C (1C = 176 mA g −1 ) and a capacity retention of 73% after 100 cycles. TCAQ is metal‐free resource abundant, acting as a sustainable cathode for ASSLIBs.